2018
DOI: 10.3389/fenvs.2018.00007
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial Farming for Environment Friendly Sustainable Agriculture Practices: Innovations and Perspectives

Abstract: Sustainable supply of food and energy without posing any threat to environment is the current demand of our society in view of continuous increase in global human population and depletion of natural resources of energy. Cyanobacteria have recently emerged as potential candidates who can fulfill abovementioned needs due to their ability to efficiently harvest solar energy and convert it into biomass by simple utilization of CO 2 , water and nutrients. During conversion of radiant energy into chemical energy, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(82 citation statements)
references
References 139 publications
(166 reference statements)
1
78
0
3
Order By: Relevance
“…As cyanobacteria do not excrete other products in any considerable amount, the cultivation process does not include any coproducts. In the case of the conversion of waste biomass to soil biofertilizer (Pathak et al., ), the avoided‐burdens (substitution allocation) method was applied.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As cyanobacteria do not excrete other products in any considerable amount, the cultivation process does not include any coproducts. In the case of the conversion of waste biomass to soil biofertilizer (Pathak et al., ), the avoided‐burdens (substitution allocation) method was applied.…”
Section: Methodsmentioning
confidence: 99%
“…A second embodiment is genetically engineered cyanobacteria that synthesize and secrete fuel molecules such as ethanol and butanol (Lan & Liao, ; Robertson et al., ). Although both cases avoid food‐ and land‐associated problems of first‐ and second‐generation biofuels (Pathak, Maurya, Singh, Häder, & Sinha, ), the cyanobacteria‐based process has been considered an improvement as, in addition to the genetic engineering tractability of cyanobacteria, a secreted product obviates the need for dewatering biomass or upgrading lipids to biofuel, which has been estimated to account for 32% of the energy input in these systems (Batan, Quinn, Willson, & Bradley, ). However, separation of secreted, short‐chain alcohols from liquid culture could also be energy‐intensive.…”
Section: Introductionmentioning
confidence: 99%
“…Photosynthesis is a multistep process comprising solar energy harvest, excitation energy transfer, energy conversion, electron transport, in particular, the transport of electrons flow from water to NADP+ and other electrochemical energy via photosystems and a series of enzymatic reactions required to synthesize components for cellular metabolism and environmental adaptation. Recently, photosynthetic prokaryotes, in comparison with plants, have attracted considerable attention for a wide range of renewable energy, agricultural and environmental applications aiming for sustainable development (Pathak, et al, 2018), probably due to their excellent productivity. However, it has been reported that the photosynthetic conversion efficiency falls around 6% of the total incident light.…”
Section: Introductionmentioning
confidence: 99%
“…The symbiotic, as well as free-living cyanobacteria, have been utilized in agricultural practices, especially in rice field. The water fern Azolla with its cyanobacterium symbiont Anabaena azollae released ammonium when inoculated in paddy field (Pathak et al, 2018). Free-living Anabaena, Nostoc, and Gloeotrichia were contributed to the productivity of rice in Chile (Pereira et al, 2009).…”
Section: Introductionmentioning
confidence: 99%